Local availability of cannabis retail outlets on parents’ cannabis use, acceptability, and perceived addictiveness: A longitudinal study in Washington State - Vi T. Le; Jennifer A. Bailey; Marina Epstein; Matthew D. Dunbar; A. Karryn Satchell; Danielle M. Pandika (PLoS ONE, 2026)
Objective Parents represent a growing yet understudied population of people who use cannabis in the era of legalization. Studies examining how increasing availability of cannabis retail stores affects parental cannabis use, norms, and perceived harm are needed to guide interventions to support families. This longitudinal study examines whether perceived and objectively measured cannabis outlet availability are associated with parents’ cannabis use frequency, acceptability, and perceived addictiveness in Washington State, where nonmedical cannabis retail stores opened in 2014. Method Parents (n = 471) in the Seattle Social Development Project – The Intergenerational Project were surveyed in 2015, 2016, and 2017. Multilevel models were used to estimate within- and between-person associations between (a) perceived cannabis outlet availability (self-reported number of outlets in one’s neighborhood) and (b) objective cannabis outlet availability (number of outlets within a 10-minute drive time from home) with past-year cannabis use frequencies, acceptability of parental cannabis use, and perceived addictiveness. Results Local retail outlet availability was higher in later waves. There were significant between-person associations, such that parents residing in neighborhoods with greater cannabis outlet availability (both perceived and objectively measured) over the course of the study had greater cannabis use frequency, higher acceptability of use, and lower perceived addictiveness. When comparing the same parents over time, the association between objectively measured outlet availability and acceptability of use was replicated in the within-person analysis, such that parents had greater acceptability of parental cannabis use in years when they lived in neighborhoods with higher objective outlet availability. Conclusions Legal cannabis retail stores are increasingly common within neighborhoods. Prevention programming to support families residing in neighborhoods with greater outlet availability may reduce permissive cannabis norms and use among parents, which can have strong implications for youth substance use prevention and positive youth development.